Regulation of SR protein localization during development - Sanford, Jeremy R. (The National Academy of Sciences, 2001)
Ser-Arg-rich (SR) proteins play numerous roles in spliceosome assembly and the regulation of splice-site selection. Whereas considerable attention has focused on the mechanistic details of SR protein activities, little is known concerning how these splicing regulators are controlled by the cell. Here we examined the subcellular localization of precursor mRNA splicing factors during early development of the nematode Ascaris lumbricoides. In the early embryo, before major zygotic gene activation, most SR proteins, along with RNA polymerase II, are localized in the cytoplasm. As development proceeds, we observe a significant decrease in the cytoplasmic levels of these factors and a concomitant increase in nuclear localization. In contrast, trimethylguanosine-capped small nuclear ribonucleoproteins are predominantly localized in the nucleus throughout this period. We previously showed that the phosphorylation state and activity of SR proteins are regulated during A. lumbricoides embryogenesis. These changes correlate with the onset of precursor mRNA splicing and zygotic transcription. Thus, a coordinate change in the subcellular localization of SR proteins and RNA polymerase II occurs at the transition from reliance on maternally deposited factors to embryonic expression. We propose that before zygotic gene activation, SR proteins and RNA polymerase II are stockpiled in the cytoplasm of early embryos, awaiting signals that lead to their activation.